Synthesis of acenaphthylene-fused heteroarenes and polyoxygenated benzo[j]fluoranthenes via a Pd-catalyzed Suzuki–Miyaura/C–H arylation cascade - Yence, Merve; Ahmadli, Dilgam; Surmeli, Damla; Karacaoğlu, Umut Mert; Pal, Sujit; Türkmen, Yunus Emre (Beilstein Journal of Organic Chemistry, 2024)
Acenaphthylene-fused heteroarenes with a variety of five- and six-membered heterocycles such as thiophene, furan, benzofuran, pyrazole, pyridine and pyrimidine were synthesized via an efficient Pd-catalyzed reaction cascade in good to high yields (45–90%). This cascade involves an initial Suzuki–Miyaura cross-coupling reaction between 1,8-dihalonaphthalenes and heteroarylboronic acids or esters, followed by an intramolecular C–H arylation under the same conditions to yield the final heterocyclic fluoranthene analogues. The method was further employed to access polyoxygenated benzo[j]fluoranthenes, which are all structurally relevant to benzo[j]fluoranthene-based fungal natural products. The effectiveness of our strategy was demonstrated via a concise, four-step synthesis of the tetramethoxybenzo[j]fluoranthene derivative 18, which represents a formal total synthesis of the fungal natural product bulgarein.
Keywords: acenaphthylene-fused heteroarenes; benzo[j]fluoranthenes; C–H arylation; fluoranthenes; heterocycles